Edutainment and practice in video-based learning: enriching educational videos with interactive activities and games. (28th February 2020) - Kleftodimos, Alexandros; Lappas, Georgios; Evangelidis, Georgios
Video-based learning has a long history but the transfer of educational videos to the web has given a powerful potential to this form of learning. Today, there is an abundance of independent educators, trainers, and educational organisations that use online video for educational content delivery. In most cases however, the videos that exist in educational platforms do not contain any aspects of interactivity and educational entertainment (edutainment). These are mostly non-interactive videos and in cases where there is interactivity this is mainly restricted to in-video quizzes and user annotations. The aim of this paper is to present solutions on how to develop interactive video-based learning environments using open source and freeware tools. In these solutions educational videos are enriched with knowledge testing activities, games, and hands-on practice exercises for learning software applications. The developed video-based learning environments were used and evaluated in classroom settings and some findings are reported in the paper.